ALOPESIA AREATA SEBAGAI SEKUELE POST REINFEKSI COVID-19 - Rudi Chandra; Djohan Djohan (Perhimpunan Dokter Spesialis Kulit dan Kelamin Indonesia (PERDOSKI), 2022)
ABSTRACT Introduction: Coronavirus disease (COVID-19) is a global pandemic that caused unprecedented morbidity and mortality. Aside from respiratory symptoms, dermatological manifestations have been widely reported, with the predominant manifestation was the hair loss. Case report: A 32-year-old male resident doctor experienced a solitary patchy alopecia areata (AA) on vertex, started 1 month after being reinfected by SARS-CoV-2. Personal history was negative for autoimmune and trichological disorders, no family history with AA. Trichoscopy examination revealed yellow dots, black dots, broken hairs, and exclamation-mark hairs. Treated with topical minoxidil and tretinoin for three months with excellent response. Discussion: The SARS-CoV-2 infection and related anxiety or emotional stress due to two times COVID-19 infections could have triggered AA. SARS-CoV-2 infection induces an activation of cytokine cascade involving interferon to disrupt hair follicle immune privilege (HFIP). Meanwhile, psychological stress enhances neurogenic inflammations and induces a shift to the immune response to type 1 T-helper cells and increases apoptosis of epithelial cells that affects hair growth. There were three prior reports about new onset AA in post COVID-19. Our report is the fourth case of new onset AA in post COVID-19, but the only case with COVID-19 reinfection. Conclusion: Our report on new onset AA in post COVID-19 reinfection provides an insight into the possible association between SARS-CoV-2 infection and AA. The onset of AA in COVID-19 patient represents a sequelae of post COVID-19 caused by immune responses or psychological distress, and there appears to be a close association in timing between them.